Антилопы рода гну (Connochaetes) в природе и в Аскании-Нова - Лобанов, Н.В.; Tpeуc, В.Д. (Вестник зоологии, 1970)
Рассматривается естественный ареал антилоп рода гну (Connochaetes), описываются условия их содержания и результаты акклиматизации в Аскании-Нова, приводятся данные об их размножении в зоопарке, результаты анализа молока С. taurinus. An areal and quantity are considered of antelopes of the genus Connochaetes in
South-Eastern Africa. In the zoo «Askaniya-Nova» C.taurinus taurinus, C.t.albojubatus,
C. gnou are maintained in enclosures with an area of 110 ha, during winter — in premises.
For 1964—1968 a progeny of 255 calves was obtained, 98 of them are passed to other institutions. As a result of long acclimatization C.taurinus changed their natural rhythm of
reproduction. The females began calving at the end of May — begining of July (90.9%).
The analysis of milk composition in C.taurinus was carried out (fat — 8.4%, total protein—6.15%).